Customer relationship management in mediating impact of customer value on customer retention in the Village Credit Institution of Denpasar Indonesia - Sadiartha, A. A. Ngurah Gede (Management and Entrepreneurship: Trends of Development, 2020)
Nowadays, business competition is very intense, which is true in the case of financial services business, including banks, Village Credit Institution and other financial service business which must always try to meet customer satisfaction. The aim of the study is to prove the need for ensuring customer satisfaction, considering its direct link with such concepts as customer retention and customer value. From empirical test result, conducted due to the research, it is obtained that customer value has a significant impact on customer retention in Village Credit Institution and that significance level of customer value significantly influences Customer Relationship Management in Village Credit Institution. In the same way, the results obtained intended that Customer Relationship Management has a significant impact on customer retention in  Village Credit Institution and it can mediate the relationship between customer value and customer retention. Taking into account the fact that Village Credit Institution is of strategic role in the well-being of the region, serving micro small enterprises (MSEs) and citizens of Denpasar through services that are carried out in accordance with customer needs, it must be managed with efficient management pattern in all fields including services.JEL Classification: M19, M21, M30, M31.